Survey of the Use of Massage for Children with Cerebral Palsy - Glew, Gwen Maureen (Multimed Inc., 2010)
BACKGROUND: Conventional medicine and complementary and alternative medicine (CAM) are merging into the broader field of “integrative medicine.” Massage is no longer considered complementary or alternative in some conventional medical circles today. PURPOSE: We aimed to determine the prevalence of massage use among children with cerebral palsy (CP) in the Pacific Northwest in the United States, the reasons that massage is being used, and the limits of recruitment for a future randomized controlled trial. METHODS: This study, the first step in a three-stage research plan, was conducted at the Neurodevelopmental and Neurology clinics at Seattle Children’s Hospital, a tertiary pediatric hospital that provides service to patients primarily from Washington, Alaska, Montana, and Idaho. As a feasibility study (stage one), it precedes a planned pilot study (stage two), and subsequently, a full-scale randomized controlled trial (stage three) of whether massage can improve the health of children with CP. The study subjects—104 families with a child with CP ranging in age from 17 months to 21 years—were surveyed by the principal investigator and a research assistant in exam rooms at the hospital. RESULTS: In the families surveyed, 80% of the children had received massage at some point. Massage was currently being used in 51%, and trained professionals were providing the massage in 23%. Most families use massage for musculoskeletal relaxation, to improve quality of life, and to help their children sleep. Lower maternal income was associated with relatives as compared with professional massage therapists providing the massage. Massage therapy use by the mother and more severe CP were significantly associated with current use of massage for the child. CONCLUSIONS: Most children with CP in the Pacific Northwest have used massage. Most parents surveyed believe that massage is helpful to their child. Additional research is needed to determine whether massage should be routinely recommended for children with CP.